Penggunaan Media Sosial Untuk Meningkatkan Kemampuan Menyimak Siswa - Sari, Rita; Anggreni, Fenny; Nurhayati, Sri; Wirduna, Wirduna (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
As a visible phenomenon where online media is one of the many correspondence media that is often used by the public in general. Likewise, the use of online media such as YouTube to further develop listening skills where students cannot listen well in Indonesian lessons, especially on the theme of living things and plants, because the teachers use boring reading stories without using learning media. So the motivation behind this goal is to see the use of web-based media such as YouTube to further develop students' listening skills. This research uses quantitative methods with the type of pre-experimental research using pretest-posttest. With a sample and population of 22 individuals. Based on data analysis using a t-test with the paired sample t-test formula, t-test using SPPS version 25. From the results of the research data it is known that (Ho) is rejected and (Ha) is accepted with a significance of t-test of 0.00 which is <0.005. Then, at that time, there was an increase in listening skills by utilizing web-based media such as YouTube.